Cerebrovascular Hemodynamics in Women - Duque, Cristina (Semin Neurol, 2017)
Sex and gender, as biological and social factors, significantly influence health outcomes. Among the biological factors, sex differences in vascular physiology may be one specific mechanism contributing to the observed differences in clinical presentation, response to treatment, and clinical outcomes in several vascular disorders. This review focuses on the cerebrovascular bed and summarizes the existing literature on sex differences in cerebrovascular hemodynamics to highlight the knowledge deficit that exists in this domain. The available evidence is used to generate mechanistically plausible and testable hypotheses to underscore the unmet need in understanding sex-specific mechanisms as targets for more effective therapeutic and preventive strategies.